Exceptional increases in fluvial sediment fluxes in a warmer and wetter High Mountain Asia - Li, Dongfeng; Lu, Xixi; Overeem, Irina; Walling, Desmond E.; Syvitski, Jaia; Kettner, Albert J.; Bookhagen, Bodo (Prof. Dr.); Zhou, Yinjun; Zhang, Ting (Science, 2021)
Rivers originating in High Mountain Asia are crucial lifelines for one-third of the world's population. These fragile headwaters are now experiencing amplified climate change, glacier melt, and permafrost thaw. Observational data from 28 headwater basins demonstrate substantial increases in both annual runoff and annual sediment fluxes across the past six decades. The increases are accelerating from the mid-1990s in response to a warmer and wetter climate. The total sediment flux from High Mountain Asia is projected to more than double by 2050 under an extreme climate change scenario. These findings have far-reaching implications for the region's hydropower, food, and environmental security.